Restricted diffusion in the splenium of the corpus callosum in organophosphate induced delayed neuropathy: case report and review of literatures - Wang, Jie (Int J Clin Exp Med, 2015)
We described a 35 year-old female who developed organophosphate induced delayed neuropathy (OPIDN) with an unusal clinical manifestation and neuroradiological presentation. Case report: A 35-year-old woman came into contact with organophosphate pesticide by remissly inhalation. She got transient unconsciousness lasting for nearly 2 hours and developed transient hematuria and hyperhidrotic subsequently. She received atropine as treatment and got a satisfying recovery and was hospital discharged without any symptoms. But 20 days later the patient displayed symptoms including headache, vertigo, mental and memory decline, and was hospitalized again. Clinical manifestations, laboratorial findings, images data will be presented. The brain magnetic resonance imaging (MRI) showed an unusal neuroradiological presentation characterized by restricted diffusion in the splenium of the corpus callosum. The patient recovered satisfactorily after administration of corticosteroids and immunogloblin. Conclusion: OPIDN may develop in some susceptible individuals even by inhalation and sometimes with central nervous system involvement. Treatment with corticosteroids and intravenous immunogloblins was found to achieve good results.